Coinage in the Name of Andragoras - Taylor , Lloyd W. H.; Wünsch , Julian (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This essay reviews recent developments in understanding of the coinage bearing the Greek legend ΑΝ∆ΡΑΓΟΡΟΥ (of Andragoras) on the reverse. The silver and gold issues of this coinage are united by the mint control on the obverse. In recent years an abundance of new examples has entered the numismatic market, increasing the available corpus of the Andragoras legend silver coinage by five-fold. Associated with this material is a newly discovered small bronze coin, probably a chalkous, or its equivalent bearing the legend ΑΝ∆ΡΑΓΟΡΟΥ accompanied by a mint control identical to one found on the preceding anepigraphic issues of Andragoras. This bronze coin establishes that in all probability the coinage issued in the name of Andragoras comprised a trimetallic currency system, struck in the denominations of a gold stater, a silver tetradrachm and a small bronze unit. This builds upon the recognition that the mint control linked imitative Athenian owl and eagle coinage that circulated alongside that bearing the legend ΑΝ∆ΡΑΓΟΡΟΥ comprised a single currency system with a structure and metrology characteristic of the mid 3rd century BC. The coins were issued by Andragoras, the Seleukid satrap, and subsequently secessionist leader of Parthia and Hyrcania. Andragoras is first mentioned, albeit without title, in an inscription from Gorgān (Hyrcania); the text names the Seleukid king Antiochos I (281-261 BC) and his wife Stratonike, indicating that Andragoras already held an official function in the 260s BC. According to Arrian (Parthica FGrHist 156 F 30), Andragoras was elevated to satrap by Antiochos II (261-246 BC). The mintage of his earliest series, the imitative Athenian owl coinage, likely commenced in the early or mid 250s BC. The coins bearing the satrap’s name were first issued around 245 BC, when Seleukid authority was weakened by the Third Syrian War against the Ptolemies and Andragoras faced the growing threat of the Parni lead by Arsakes. When the steppe warriors invaded Parthia around 240 BC, they killed Andragoras and thus ended his short-lived revolt.